Text-based E-contact: Harnessing cooperative Internet interactions to bridge the social and psychological divide. Issue 1 (1st January 2020) - White, Fiona A.; Maunder, Rachel; Verrelli, Stefano
ABSTRACT: In order to bridge the psychological and physical divide between different groups, researchers have harnessed the positive elements of the Internet to improve intergroup contact. One new and effective Internet strategy is Electronic- or E-contact. Unlike other contact approaches, E-contact is an experimental intergroup intervention that uniquely accommodates Allport's contact theory and recategorisation processes, to create a structured, cooperative, synchronous and goal-directed online text interaction between members from different groups. E-contact has been found to successfully improve intergroup relations between Catholics and Protestants in Northern Ireland and Muslims and Catholics in Australia; and reduce bias against lesbian women and gay men, people with schizophrenia, Indigenous Australians, and transgender individuals. This paper discusses the unique engineering and advantages of E-contact interventions in comparison to existing contact strategies, identifies the theories that guide E-contact interventions, provides meta-analytic evidence of its effects, and discusses the strengths, limitations and future directions for E-contact research.